X-Linked Agammaglobulinemia Presenting as Neutropenia: Case Report and an Overview of Literature - Lanlokun, Mosopefoluwa; Borden, Amanda; Nieves, Daime; Walter, Jolan E.; Albright, Deborah (Frontiers in Pediatrics, 2021)
X-linked agammaglobulinemia (XLA) is an inherited immunodeficiency caused by mutations in the Bruton Tyrosine Kinase (BTK) gene. Neutropenia is an important feature of and may be the initial abnormal laboratory finding for some patients with XLA. Though the pathophysiology of neutropenia in patients with XLA has not yet been well described, the two cases presented below strongly support evaluation for immunodeficiency in otherwise unexplained neutropenia in the setting of infections, particularly if they are male patients. Timely consideration of XLA in the population of neutropenic patients may also prevent invasive bone marrow biopsy that occurred for both cases in our report.